Screening of simple sequence repeats (SSR) primers from mutated Indigofera zolligeriana Miq plants. Issue 1 (1st December 2022) - Royani, J I; Sinaga, O F Br; Aliyah, K N; Hardianto, D; Agustina, T; Rofiq, M N; Kristamtini; Handayani, T; Puspitasari, W; Sudarsono; Abdullah, L; Asiyah, S I
Abstract: The mutated plants from Indigofera zolligeriana were screened using 14 SSR primers, to know the polymorphic DNA profiles of mutated plants. For screening these primers we used 12 DNA genomes of mutated I. zolligeriana plants. DNA genomes from 12 mutated plants were isolated. Amplification of 12 DNA genomes using multiplex PCR method followed by optimization of the method to obtain the best band profiles. Screening with the 14 SSR primers showed that not of the 14 primers used could amplify DNA genomes of mutated I. zollingeriana. Five primers showed polymorphic bands at 59°C and 13 primers at 48°C. After all treatments, 12 primers are suitable for use in further DNA profiling of other mutated I. zolligeriana plants.